Outcomes of elective cancer surgery in COVID‐19 survivors: An observational study. Issue 1 (16th September 2022) - Ranganathan, Priya; Salunke, Bindiya; Wajekar, Anjana; Siddique, Aafreen; Daruwalla, Kaizeen; Chawathey, Shreyas; Niyogi, Devayani; Nayak, Prakash; Divatia, Jigeeshu
Abstract: Background and Objectives: Guidelines recommend deferral of elective surgery after COVID‐19. Delays in cancer surgeries may affect outcomes. We examined perioperative outcomes of elective cancer surgery in COVID‐19 survivors. The primary objective was 30‐day all‐cause postoperative mortality. The secondary objectives were 30‐day morbidity, and its association with COVID‐19 severity, and duration between COVID‐19 and surgery. Methods: We collected data on age, gender, comorbidities, COVID‐19 severity, preoperative investigations, surgery performed, and intra and postoperative outcomes in COVID‐19 survivors who underwent elective cancer surgery at a tertiary‐referral cancer center. Results: Three hundred and forty‐eight COVID‐19 survivors presented for elective cancer surgery. Of these, 332/348 (95%) patients had mild COVID‐19 and 311 (89%) patients underwent surgery. Among patients with repeat investigations, computerized tomography scan of the thorax showed the maximum new abnormalities (30/157, 19%). The 30‐day all‐cause mortality was 0.03% (1/311) and 30‐day morbidity was 17% (54/311). On multivariable analysis, moderate versus mild COVID‐19 (odds ratio [OR]: 1.95; 95% confidence interval  [CI]: 0.52–7.30; p  = 0.32) and surgery within 7 weeks of COVID‐19 (OR: 0.61; 95% CI: 0.33–1.11; p  = 0.10) were not associated with postoperative morbidity. Conclusions: In patients who recover from mild to moderate COVID‐19, elective cancer surgery can proceed safely even within 7 weeks. Additional preoperative tests may not be indicated in these patients.